TELAAH PEMIKIRIAN YUSUF AL-QARDHAWY (STUDI LITERATUR TENTANG PERILAKU PENIMBUNAN BARANG DI MASA COVID 19) - MUKHLIS ILIS (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the relevance of Yusuf Al-qardhawy's thoughts about ihtikar with the conditions of the Covid19 Pandemic in Indonesia. The approach of this research is carried out by the method of literature review and action activities that occur in the world of trade and business related to current research. The negative impact caused by speculators in the economy resulted in trampling the world market and the price instability that occurred in society became difficult. The phenomenon of hoarding often occurs everywhere, including staples and other community needs. With the vast territory of Indonesia, there are various provinces and municipalities, so that prices on the market will never be stable. With the volatility of prices in the market, there is a frequent use of market opportunities to commit fraud, manipulation, fraud and hoarding often occur in the market. The concept of price stability from the government will never be ignored by business people, markets and swords. Market forces affect the entire buying and selling component, causing goods to frequently disappear from the market. This research provides a broad overview in interpreting ihtikar, moving on from the thoughts of Syeikhul Yusuf Al-qardhawy. Yusuf Al-Qardhawy's thought explains that the act of ihtikar is one of the sins and prohibits all forms of hoarding to be done for both primary and secondary needs. and tertiary. His views are more systematic and detailed in understanding Ihtikar. Analysis of Yusuf Al-Qardhawy's thought in the present context is very appropriate that ihtikar actors can be rewarded or punished in this Republic. Government policies are urgently needed to realize penalties for people who always hoard goods both on a small and large scale.